DEVELOPING A PROGRAM TO ENHANCE CREATIVE LEADERSHIP OF SCHOOL ADMINISTRATORS UNDER THE NAKHON RATCHASIMA PRIMARY EDUCATIONAL SERVICE AREA OFFICE 6 - Hanprachum, Paknapa; Julsuwan, Suwat (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The research article was 1) to study the current situation, Desirable condition and needs 2) develop a program to enhance creative leadership of school Administrators Under the Nakhon Ratchasima Primary Educational Service Area Office 6, this research The research was divided into 2 phases: Phase 1, the study of current conditions. Desirable conditions and necessities of enhancing creative leadership of school administrators. The sample group used for data collection were 290 school administrators and teachers. The instrument used for data collection was a questionnaire which include 60 items in a 5-point rating scale format with a power of discrimination from 0.30-0.86 and reliability value from 0.98-0.99. The statistics used for data analysis were frequency, percentage, mean, standard deviation. and the Essential Needs Index. Phase 2, the development of programs to enhance creative leadership of school administrators. The group of informants consisted of 5 experts. The tool used to collect data was the assessment form. The result of the research revealed that: 1. The present condition of enhancing creative leadership of educational institution administrators under the Office of Nakhon Ratchasima Primary Educational Service Area 6, the overall level was at a high level. For the desirable condition of enhancing creative leadership of educational institution administrators Under the Office of Nakhon Ratchasima Primary Educational Service Area 6, overall, it was at the highest level. and the order of needs and necessities in developing creative leadership of educational institution administrators. The most demanding for development, followed by flexibility and adaptability, and teamwork. and in regard to individuality, respectively.2. The results of the development of the program to enhance creative leadership of the school administrators Under the Nakhon Ratchasima Primary Educational Service Area Office 6, it was found that the program was appropriate and the feasibility was at the highest level.